'Intersectionality Went Viral': Toxic Platforms, Distinctive Black Cyberfeminism and Fighting Misogynoir – An Interview with Kishonna Gray. (17th March 2020) - ,
Dr Kishonna L. Gray is Assistant Professor in Communication and Gender and Women's Studies at University of Illinois in Chicago, and Faculty Associate of Berkman-Klein Center for Internet and Society at Harvard University. She is the author of Race, Gender, and Deviance in Xbox Live (Gray, 2014 ) and the co-editor of two books on gaming and culture Feminism in Play (Gray, Vorhees and Vossen, 2018 ) and Woke Gaming (Gray and Leonard, 2018 ) which looks at the potential of video games for instigating social change and justice. As well as publishing in academic journals, she also has an active blog and a podcast. In this interview WPCC asks Dr Gray to consider the viral aspects to the spread of intersectionality discourse and whether commercial social media platforms have been, in the end, hospitable to 'voice to anti-racist, anti-misogynist narratives?' Opportunities within viral digital culture for users of colour and women, the characteristics of digital feminism, #BlackLivesMatter, Black Cyberfeminism and digital inequality are other topics covered.